Training on the Utilization of Water Hyacinth Waste into Handicraft Products for PKK Women in Tambak Oso Village, Sidoarjo - Dyan Agustin; Niniek Anggriani; Aprilia Shyntia Dewi; Fransiska Oktiviani .C. I (Nusantara Science and Technology Proceedings, 2022)
Tambak Oso Village is a densely populated village and is traversed by one large river, the Buntung River. Currently, the Buntung River is silting up and full of water hyacinth, which causes various problems, including flooding, a reduced number of fish, and damage to the propellers of fishing boats. To reduce the presence of water hyacinth waste, training efforts are needed to process it into handicraft products, including placemats, trays, flower vases, tissue boxes, pencil cases, and other household knick-knacks. The technique used uses a plaiting technique and sticks because it is easy to do, the results are good and it does not require expensive tools. For the human resources who carry out this activity, PKK women, whose daily activities are usually only at home, sometimes help process fish ponds and catch fish. The method used in this training is divided into 2 stages. The first is counseling on how to process water hyacinth materials from taking the river to dry raw materials. The second is training on making handicraft products from water hyacinth waste using woven techniques. At this stage, they also showed examples of product designs for woven crafts from water hyacinth, which are good for exploring creativity with products including household appliances such as placemats, trays, flower vases, tissue boxes, and pencil cases. The results obtained from this service activity improve the skills of PKK members so that they can increase household income and reduce the problem of water hyacinth waste that fills the Buntung river in Tambak Oso Village, Sidoarjo, and can make Tambak Oso village better known and can later become a tourist village.